(untitled) (Environment & Health, 2015)
Objective. We estimated a level of the functional state of cardiovascular system (CVS) and physical work capacity by the results of bicycle exercise (BE) in the subway electric locomotive operators (ELOs). Materials and Methods. Males, including 30 ELOs (main group) and 20 engineers (control group), were examined. According to age and work experience, the examined persons of the main group were divided into 3 subgroups: 7 persons — till 30 years old with a work experience till 5 years (23,3%) — the 1-st subgroup; 17 persons — 30-40 years old with the work experience of 5-10 years (56,7%) — the 2-nd subgroup; 6 persons — over 40 years old with work experience over 10 years (20,0%) — the 3-rd subgroup. According to age and work experience, the examined persons of the control group were also divided into 3 subgroups: 5 persons— till 30 years old with the work experience till 5 years (25,0%) — the 1-st subgroup; 10 persons — 30-40 years old with a work experience of -10 years (50,0%) — the 2-nd subgroup; 5 person — of the examined ones, the 3-rd subgroup. Submaximal load was performed. While carrying out the BE, we fixed the values of heart rate, systolic and diastolic blood pressure (BP), values at any degree of exercise, their initial level and results of the measurements at any exercise rate. We registered a time needed for the restoration of these parameters after exercises and also assessed a tolerance to physical exercises (TPE) and physical work capacity (PWC 170). A level of energy resources in myocardium was determined with the calculation of the Robinson’s index. Results and Discussion. Results of the research demonstrate that all examined ELOs (100%) had no organic diseases of the CVS according to the BE data. Taking into account the BE results of the ELOs (heart rate and BP, at rest, and at any degree of exercises and after the exercises) it is possible to tell about sympathicotonia in the ELOs. Exercise tolerance and level of physical work capacity were estimated under the PWC 170 test. The ELOs, who were younger than 30 years with a work experience till 5 years, had the highest indices in comparison with those who were 30-40 years old with the work experience of 5 10 years and who were over 40 years old with the work the experience over 10 years. It may be connected with a longterm impact of stress factor on their organism and harmful occupational conditions. The Robinson’s index in the ELOs who are younger than 30 years with a work experience till 5 years testifies about their high level of somatic health. In those ELOs who are 30-40 years old with a work experience of 5-10 years it testifies about an average level of somatic health and in those who are over 40 years old with the work experience over 10 years it testifies about a level of somatic health which is lower than an average one. Conclusions. There is a vegetative imbalance with sympathicotonia predomination in the ELOs, it can be a risk for the CVS diseases in the ELOs.